2021
DOI: 10.1186/s12964-021-00768-1
|View full text |Cite
|
Sign up to set email alerts
|

Cancer derived exosomes induce macrophages immunosuppressive polarization to promote bladder cancer progression

Abstract: Background Exosomes mediated crosstalk between tumor cells and other stromal cells including tumor associated macrophages plays an essential role in reprogramming tumor microenvironment (TME) to facilitate tumor progression. However, the mechanism of tumor derived exosomes promotes bladder cancer progression have not been defined. Methods Exosomes were extracted from bladder cancer cells MB49 conditioned medium by ultracentrifugation. The effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Therefore, we reasoned that the secreted WT cancer cell-derived exosomes might be involved in macrophage programming, as has been suggested in previous studies (43,44). Accordingly, EVs were isolated from WT and FMRP-KO PDAC cancer cells (fig.…”
Section: Distinctive Phenotypes Of Macrophages Populating Wt Versus K...mentioning
confidence: 90%
“…Therefore, we reasoned that the secreted WT cancer cell-derived exosomes might be involved in macrophage programming, as has been suggested in previous studies (43,44). Accordingly, EVs were isolated from WT and FMRP-KO PDAC cancer cells (fig.…”
Section: Distinctive Phenotypes Of Macrophages Populating Wt Versus K...mentioning
confidence: 90%
“…Tumor-derived exosomes can be taken up by macrophages in the tumor microenvironment and then participate in tumor progression and metastasis ( Baig et al, 2020 ). Bladder cancer derived exosomes induced macrophage M2 polarization to facilitate bladder cancer progression ( Jiang et al, 2021 ). Macrophages were reported to exhibit M1 and M2 subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that TAMs accumulate in the tissue of GICs due to cancer-released mediators such as CCL-2 and CSF1, which recruit MΊs to infiltrate tumor tissues. 17 , 38 , 39 Several pieces of evidence highlighted the role of Exos released by cancer cells in the intracellular communication between TAMs and tumor cells, thus promoting M2 polarization, 40 , 41 as shown in Figure 1 . Tumor cell-derived Exos transfer many molecules into TAMs such as oncoproteins, miRNAs, lncRNAs, circRNAs, and lipids that actively mediate polarization into M2 and thus enhancing tumor progression.…”
Section: Interaction Between Gic and M2-tams-exos-ncrnas In The Tmementioning
confidence: 99%